IM-3 IDENTIFICATION OF THERAPEUTIC TARGET ANTIGENS USING PATIENT DERIVED GLIOBLASTOMA AND THEIR APPLICATION TO CAR-T THERAPY. (3rd December 2022) - Kuroda, Hideki; Kijima, Noriyuki; Tachi, Tetsuro; Utsugi, Rena; HIrayama, Ryuichi; Okita, Yoshiko; Kagawa, Maoki; Hosen, Naoki; Kishima, Haruhiko
Abstract: Introduction: Recently, CAR-T cell (chimertic antigen receptor T-cell) therapy has been attracting and has shown high therapeutic efficacy, especially in the hematological tumors. The T cells from patient are then genetically engineered to specifically bind to and attack the target tumor cell antigen. In the brain, EGFRvIII or HER2 have been used as antigens, but have yet to show positive results. It is necessary to find antibodies that are more specific and have a therapeutic effect. Methods: A primary culture line was prepared from glioblastoma surgical specimens, and immunized to Balb/c mice with it.The B cells from the mice were fused with myeloma cells, immortalized, and cultured monoclonally to obtain a number of monoclonal antibodies reacted glioblastoma cells. The obtained antibodies were reacted with glioblastoma cells and normal brain cells, and those that specifically react to glioblastoma were selected by flowcytometry to obtain antibody candidates that could be specifically expressed on the surface of glioblastoma cells. Results: Approximately 20, 000 antibody-producing strains were generated. From these, about 3, 200 strains were selected as the reacted with immunized glioblastoma. About 560 strains was selected that reacted with at least one other glioblastoma, and from these, we selected 30 strains that did not react with normal brain cells. Finally, the cells were frozen and thawed at least once, and 13 stably growing strains selected. Discussion: We have been identified one antibody among approximately 500 strains in past our study, and have confirmed that it is B7H3, a pan-tumor antibody. We will generate more antibody candidates in the future, as well as identify antibodies in 13 strains that have already been selected and confirmed to be glioblastoma-specific antibodies. We will also create CAR-T cells targeting these antibodies and confirm their anti-tumor effects.